GENERAL CHARACTERISTICS OF PHRASEOLOGICAL UNITS AND THEIR USAGE IN LITERATURE - Xudashukur Abdiyev Karimboy ugli (Journal of new century innovations, 2023)
Phraseological units are expressions consisting of multiple words with a fixed, non-compositional structure that convey a particular idea or concept. They are commonly used in language to express ideas that cannot be conveyed through individual words. The key characteristics of phraseological units include their stability, idiosyncratic meaning, and irregularity in grammatical structure. These expressions are considered stable because they cannot be easily altered without losing their original meaning. Their meaning is often unique and not always predictable based on the meanings of the individual words within the phrase. Furthermore, phraseological units often do not follow regular syntax rules, which can make them challenging for learners of a new language to understand.